Antifeedant activity of Vernonia oocephala against stored product pest Tribolium casteneum (Herbst) (Bangladesh Journal of Scientific and Industrial Research, 2015)
In recent years botanical antifeedants have received increasing attention in developing countries due to continued damaging of grains associated to post harvest insect pest. To develop a sustainable management of post harvest pest using local plant resources in Nigeria, Vernonia oocephala ethanol extract, chloroform and petroleum ether fractions were subjected to antifeedant activity against the stored product pest (in maize and maize flour products) Tribolium casteneum (Herbst). Wheat wafer disc technique was used in the experiment. The feeding deterrence expressed as Feeding inhibition rate [FI] (%), indicates that ethanol extract was most potent against the insect with a range of 54±1.43 to 86±1.2% and moderate activity of 50±1.11 to 70±3.12% was observed in the chloroform fraction. Phytochemical screening revealed the presence of flavonoids, glycoside, saponins, steroids and triterpenes, cardiac glycoside and tannins in addition; sesquiterpene lactones were identified from chloroform fraction. These findings indicate the potential utility of extracts and fraction of Vernonia oocephala for developing active botanical pesticides against the pest Tribolium casteneum DOI: http://dx.doi.org/10.3329/bjsir.v49i4.22627 Bangladesh J. Sci. Ind. Res. 49(4), 243-248, 2014